2001
DOI: 10.1002/jca.1021
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic studies during peripheral blood stem cell collection show CD34+ cell recruitment intra‐apheresis

Abstract: A sufficient number of CD34+ cells in the peripheral blood stem cell product is important to achieve a rapid and sustained engraftment. The purpose of the present work was to study CD34+ cell kinetics during leukapheresis. Blood samples before and after leukapheresis were analysed for CD34+ cells in 205 procedures. The number of CD34+ cells after plus the number of CD34+ cells harvested was 1.5-fold greater than the number available at the beginning of the procedure, indicating recruitment of CD34+ cells durin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(11 citation statements)
references
References 12 publications
1
10
0
Order By: Relevance
“…We also observed that pre‐apheresis CD34 + cell count was associated with CD34 + cell yield per liter of PBV, which was consistent with previously described data on utilization of Spectra Optia cMNC protocol in autologous LVL procedures 21,29 . LVL has been widely performed in patients and reported to collect increased number of CD34 + cells compared to NVL, 19,22,25 since CD34 + cells could be recruited to the peripheral blood during leukapheresis 13,39 . Based on the kinetics of CD34 + cell in peripheral blood after G‐CSF administration, 2–5 leukapheresis is usually commenced on day 5 of G‐CSF injection in donors 8,9,12 .…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…We also observed that pre‐apheresis CD34 + cell count was associated with CD34 + cell yield per liter of PBV, which was consistent with previously described data on utilization of Spectra Optia cMNC protocol in autologous LVL procedures 21,29 . LVL has been widely performed in patients and reported to collect increased number of CD34 + cells compared to NVL, 19,22,25 since CD34 + cells could be recruited to the peripheral blood during leukapheresis 13,39 . Based on the kinetics of CD34 + cell in peripheral blood after G‐CSF administration, 2–5 leukapheresis is usually commenced on day 5 of G‐CSF injection in donors 8,9,12 .…”
Section: Discussionsupporting
confidence: 89%
“…A recent study presented the evidence that circulating CD34 + cell count rapidly decreased to a relative equilibrium level 44 . However, previous studies have suggested that CD34 + cells could be recruited during leukapheresis 13,39 . Therefore, we might have underestimated the actual CE values.…”
Section: Discussionmentioning
confidence: 91%
“…To investigate if these findings could partially be explained by RF, we modified the initial formula described by Knudsen et al [16] in a similar manner to the formula for cell loss and considered the positive fluid balance of the donor at the end of the leukapheresis. The mean values and the ranges of the RF are demonstrated in table 4.…”
Section: Resultsmentioning
confidence: 99%
“…28,29 Despite technological advances, machines still allow for the operator to adjust preferences to reduce further RBC contamination or to improve when necessary collection yield when cell counts are relatively small. [30][31][32] This is something that is facilitated by the platform's software management system. 33 Even though this could be seen as leading to every collection being modified by the operator, this is not the case since greater contamination by other cell types of the product can occur in this way requiring additional manipulation and processing of the product including collection of additional plasma to aid in cryopreservation.…”
Section: Procedures Durationmentioning
confidence: 99%
“…This lower platelet removal is particularly important for patients who, because of their disease state or therapy, have platelet counts in the low or low‐normal range at the start of collection 28,29 . Despite technological advances, machines still allow for the operator to adjust preferences to reduce further RBC contamination or to improve when necessary collection yield when cell counts are relatively small 30–32 . This is something that is facilitated by the platform's software management system 33 .…”
Section: Cell Collectionsmentioning
confidence: 99%